2005
DOI: 10.1242/jcs.02376
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Ca2+ sensor protein VILIP-1 affects cGMP signalling of guanylyl cyclase B by regulating clathrin-dependent receptor recycling in hippocampal neurons

Abstract: . Recently, it has been shown that the NCS protein VILIP-1 influences the activity of the receptor guanylyl cyclase GC-B. In transfected cell lines, VILIP-1 performs a Ca 2+ -dependent membrane association, the reversible Ca 2+ -myristoyl switch of VILIP-1, which leads to an increase in natriuretic peptidestimulated cGMP levels. In this study, we have investigated the effect of VILIP-1 on cGMP signalling in C6 cells and in primary hippocampal neurons, where VILIP-1 and GC-B are co-expressed in many but not all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 45 publications
2
73
0
Order By: Relevance
“…These data demonstrate that VILIP-1 is a key regulator of NPR-B signalling in cardiomyocytes by modulating the amount of receptor molecules in the membrane. This is in accordance with previous studies demonstrating that VILIP-1 may either directly interact with NPR-B or alter clathrin-dependent membrane trafficking of NPR-B in C6 glioma cells [9,28].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data demonstrate that VILIP-1 is a key regulator of NPR-B signalling in cardiomyocytes by modulating the amount of receptor molecules in the membrane. This is in accordance with previous studies demonstrating that VILIP-1 may either directly interact with NPR-B or alter clathrin-dependent membrane trafficking of NPR-B in C6 glioma cells [9,28].…”
Section: Discussionsupporting
confidence: 93%
“…These effects are possibly mediated by actions on membrane receptors and ion channels such as the natriuretic peptide receptor B (NPR-B) and the nicotinic acetylcholine receptor [9,10]. VILIP-1 modulates clathrin-dependent receptor cycling in the central nervous system supporting its general role in membrane trafficking [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VILIP-1 has been found to regulate a class of purinergic receptors (Chaumont et al 2008). They have been shown to have effects on gene expression and are also involved in traffic of proteins to the plasma membrane Brackmann et al 2005). Hippocalcin has been suggested to be involved as a Ca 2þ sensor in long term depression in hippocampal neurons (Palmer et al 2005) and shows a Ca 2þ /myristoyl switch for translocation within such neurons (Markova et al 2008).…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 99%
“…DREAM is a member of NCS family, which is divided into five subfamilies: recoverins, guanylate cyclase activating proteins (GCAPs), frequenin (NCS-1), visinin-like protein (VSNL), and KChIP (Burgoyne, 2007). A general role for NCS proteins in membrane transport and receptor trafficking is supported by a variety of studies (Weiss et al, 2000;Lin et al, 2002;Brackmann et al, 2005;Haynes et al, 2005;Palmer et al, 2005), and direct interactions have been revealed between NCS proteins and molecules involved in membrane trafficking (Ivings et al, 2002;Palmer et al, 2005). It has been reported that visinin-like protein 1 (VILIP-1) and VILIP-3 form a complex with the GluR6 subunit of kainite receptors (Coussen et al, 2005), although the functional effect of this complex is unknown.…”
Section: Discussionmentioning
confidence: 99%